Financial Inclusion: The Road Ahead for Women Entrepreneurs - Karlapathi, Vishnupriya Hymavathi; Nanduri, Dr. Sireesha (The journal of contemporary issues in business and government, 2022)
An entrepreneur is an individual who tries to utilize the maximum available resource to attain maximum gain. Entrepreneurial behaviour is often motivated by a variety of factors, including a desire for personal achievement, a goal for financial gain, and a motive to help others. Countries worldwide have understood the importance of entrepreneurship and provided opportunities to women to start ventures that improve the country’s economic growth and raise living standards. According to National Statistical Office (NSO), 2021, the literacy rate in India is 77.75%, the male literacy rate is 84.70%, and women with 70.30%. Women contribute 48.36% of the Indian population, but participation in economic activity has declined to 16.1% due to the COVID crisis. In this paper, we tried to explore the significant challenges that Women Entrepreneurs faced during the world’s major pandemic, COVID-19, and propose the suggestions that would help create the policies that allow women entrepreneurs to consider the uncertain effects faced during the pandemics.